Asymmetric Synthesis of Oxa‐Bridged Oxazocines through a Catalytic RhII/ZnII Relay [4+3] Cycloaddition Reaction. Issue 51 (6th November 2019) - Xu, Chaoran; Wang, Kaixuan; Li, Dawei; Lin, Lili; Feng, Xiaoming
Abstract: Oxa‐bridged oxazocines bearing three chiral carbon centers were synthesized efficiently through a bimetallic catalytic asymmetric tandem reaction of β, γ‐unsaturated α‐ketoesters with diazoimides. The process contained a rhodium‐promoted in situ generation of isomünchnone from diazoimide decomposition, and a [4+3]‐cycloaddition of β, γ‐unsaturated α‐ketoester catalyzed by a chiral N, N′ ‐dioxide‐Zn II complex. Ligand‐accelerated catalysis was found, and a possible transition‐state model was proposed to explain the origin of stereoselectivity. Abstract : A highly efficient asymmetric cascade reaction of β, γ‐unsaturated α‐ketoesters and diazoimides was realized by using a bimetallic rhodium(II)/chiral N, N ′‐dioxide‐zinc(II) catalytic system. The corresponding oxa‐bridged oxazocine products bearing different substituents were obtained in moderate to excellent yields with excellent enantioselectivity under mild reaction conditions.